Rethinking Indigenous policing on reservation lands in Canada: Reflections from Australia and the United States - Westlund, Shayna (Author); Aulakh, Harpreet (Thesis advisor); Mount Royal Uiversity Economics, Justice, and Policy Studies (Degree granting institution)
The historical relationship between the Indigenous Peoples of Canada and the federal government is strained as they have been subjected to continuous and ongoing injustices. To address various issues associated with Indigenous Peoples and the justice system, First Nations Policing Programs were introduced. Extensive research has been conducted evaluating Canada's Indigenous policing practices; however, there are gaps in the literature pertaining to best practices and what can be improved. This research aims to highlight the strengths and shortcomings of Canada's FNPP and Indigenous policing practices while reflecting on the Indigenous policing practices observed in Australia and the United States in an effort to determine the best and actionable practices that can be implemented in Canada. Through a descriptive analysis of purposively selected literature, this research suggests that Indigenous policing in Canada can be enhanced by redefining its services, implementing community patrols similar to what is employed in Australian Indigenous communities, and securing adequate funding. Additionally, further research evaluating Indigenous policing in Australia and the United States is necessary.